You Are What You Eat. Television narratives between hedonism and self-control - Stagi, Luisa (Italian Sociological Review, 2013)
Television programming has experienced a recent influx of shows which focus on food and diet. The discursive forms employed by the media converge on an axis of hedonism/self-control: on the one hand, the increased construction of a culture of desire and fantasy relating to the consumption of food (Food Porn), on the other a neo-liberal discourse on the privatization of the individual’s responsibility towards their own body and health by virtue of media spectacularization of self-empowerment and self-governance.